2007
DOI: 10.1002/anie.200604837
|View full text |Cite
|
Sign up to set email alerts
|

A Multifunctional Light Switch: DNA Binding and Cleavage Properties of a Heterobimetallic Ruthenium–Rhenium Dipyridophenazine Complex

Abstract: The "DNA light switch" [Ru(phen) 2 (dppz)] 2+ (1; dppz = dipyrido[3,2-a:2',3'-c]phenazine, phen = 1,10-phenanthroline) has attracted particular attention, as it displays a huge luminescence enhancement (> 10 4 ) upon intercalation into DNA.[2] The excited states of such systems are insufficiently oxidizing to cleave DNA directly, and although they can generate singlet oxygen [3] -a species that can cause DNA damage and even some cleavage [4] -this process has low quantum yields, particularly for intercalated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(60 citation statements)
references
References 26 publications
0
57
0
1
Order By: Relevance
“…The mitochondria-specificity has been confirmed with co-localisation experiments using TMRE, which is known to accumulate in mitochondria. The first class of luminescent biotinylation reagents, derived from rhenium(I) polypyridine complexes [Re(N^N)(CO) 3 (py-biotin-NCS)] + (24), have been reported by Lo and co-workers [62]. To investigate the amine-specific reactivity + (25).…”
Section: Cellular Probesmentioning
confidence: 99%
See 1 more Smart Citation
“…The mitochondria-specificity has been confirmed with co-localisation experiments using TMRE, which is known to accumulate in mitochondria. The first class of luminescent biotinylation reagents, derived from rhenium(I) polypyridine complexes [Re(N^N)(CO) 3 (py-biotin-NCS)] + (24), have been reported by Lo and co-workers [62]. To investigate the amine-specific reactivity + (25).…”
Section: Cellular Probesmentioning
confidence: 99%
“…Thus, initially at least, the complex functions as a monointercalating system and the second rhenium centre may be free to interact with other DNA duplexes (interstrand binding). Recently, a related heterobimetallic complex [{Ru(tpm)(dppz)(m-dpp [5])(CO) 3 Re(dppz)}] 3+ (5) has been isolated that possesses both DNA-light switch and photocleavage properties [24].…”
Section: (L)]mentioning
confidence: 99%
“…[30,31] These units have provided more facile methods toward the synthesis of oligomeric metallo-intercalators. [32][33][34] Given the proven therapeutic potential of the Ru II dppn-moiety, we set out to synthesize dinuclear systems that incorporate this unit and, for the first time, the syntheses of both dinuclear homoleptic (Ru II dppn) and heteroleptic (Ru II (dppz)/Ru II (dppn)) complexes are described. In the initial studies reported herein we also compare the photophysical and cell-based biological properties of these new complexes with their Ru II dppz analogues.…”
Section: +mentioning
confidence: 99%
“…Recent developments include the consideration of bimetallic complexes, such as 13e, where a hypsochromic shift in both the MLCT and IL transitions when added to buffered DNA [124]. Studies with the hetero-dinuclear complex 13f reveal energy transfer between the Re(I) and the Ru(II) centres, and a light-switch behaviour in the emission on the introduction of DNA [125].…”
Section: Detection Of Dnamentioning
confidence: 99%